(untitled) (Dhaka University Journal of Biological Sciences, 2019)
Samples of Drosophila species were collected from some selected sites (viz., Dohar Upazila of Dhaka Division, Hironpoint of the Sundarbans, Satchori of Sylhet Division) of Bangladesh and these were cultured in the laboratory to study developmental stages, external morphological traits and sex comb. They were identified as D. melanogaster, D. ananassae and D. bipectinata. The sex comb teeth number and arrangement were distinct for all three species. D. melanogaster had one row of 10 - 11 teeth in the sex comb. D. ananassae had eight rows of teeth in the sex comb possessing 32 - 33 teeth in total. D. bipectinata had 2 - 3 rows of teeth in the sex comb and total teeth number varied from 11 to 15. Among three species, sex comb teeth number of D. bipectinata varied most. Eleven different patterns (n=20) in sex comb were observed in D. bipectinata indicating significant diversity within species. Variation in pupation sites among three species was also observed in the laboratory condition. D. bipectinata pupated on the food medium, whereas other two species pupated on the vial wall. Thus, diversity among these three species of Drosophila was documented which could be utilized as bioindicator in future. Dhaka Univ. J. Biol. Sci. 28(2): 167-176, 2019 (July)